Penyelesaian Wanprestasi pada Perjanjian Sewa Beli Sepeda Motor Bekas di UD.MBS-Motor - Sinaga, Sangap Mangatur; Heriyanti, Yuli; Sutrisno, Hafiz (PT PUSTAKA CENDEKIA GROUP, 2023)
The need for transportation is very important both for transportation of school children and even for business purposes. One of the transportation needs is a motorbike. For some people the need to own a motorbike can be fulfilled easily but for some it is still difficult because of economic limitations. As a result of the community's purchasing ability in cash is reduced, then there is a sale and purchase in installments with a lease and purchase agreement, which can cause default problems. settlement of the price of the goods that have been mutually agreed upon and which is bound in an agreement and the ownership rights to the goods are only transferred from the seller to the buyer after the total price has been paid in full by the buyer to the seller. at UD. MBS-Motor, namely: What are the factors that cause default in the motor vehicle rental agreement and what is the form of settlement of the default in the used motorcycle rental agreement at UD. MBS-Motor. This research was conducted using the observation method by collecting data by direct question-and-answer interviews with debtors who defaulted and samples were taken randomly as much as 10% of the sample population, and data collection was also carried out by interviewing parties. company. From the direct research results obtained several factors that cause default, namely socio-economic factors and the existence of bad faith from the debtor. Problem solving in the motor vehicle rental agreement at UD. MBS-Motor usually uses two methods, namely by deliberation to reach consensus, and by court lawsuits, but in practice it often uses the deliberation and consensus method, because it is considered more effective and less complicated, unless the tenant really does not want to be responsible for the mistakes that have been made he did.